Embryonic ontogeny of three species of Horned Frogs, with a review of early development in Ceratophryidae - Grosso, Jimena Renee (2019)
Horned Frogs of the family Ceratophryidae are conspicuous anurans represented bythree endemic South American genera. Most ceratophryids inhabit semiaridenvironments, but three species of Ceratophrys occupy tropical or temperate humid areas.Several morphological and behavioral characters of larvae and adults are conserved across the family. Based on examination of specimens and accounts in the literature, the embryonic development of C. ornata, C. cranwelli, and the monotypic genus Chacophrys are described and compared with that of species of Lepidobatrachus. Ceratophryid embryos share a suite of morphological features and heterochronic shifts during development. Most features, such as gill structure, ciliation, early hatching, and precocious differentiation of the gut and hind limbs, are shared by all the species regardless the differences in the habitats that occupy. This is consistent with previous observations of some adult characters, and likely supports the hypothesis of an early diversification of ceratophryids in semiarid environments. Other embryonic features, such as the morphology and ontogeny of the oral disc and digestive tract, are correlated with larval feeding habits and vary within the family. The evolutionary and ecological significance of some conserved characters (e.g., gastrulation pattern, Type-A adhesive glands) and other taxon-specific features (e.g., nasal appendix) remain to be explored in the group.